Study of antioxidant activity of selected monocarbohydrazone derivatives - Gorana Mrđan; Borko Matijević; Sanja Vlaisavljević; Đenđi Vaštag; Suzana Apostolov (Zaštita Materijala, 2021)
Many of carbohydrazone derivatives have shown a wide range of biological activities. In previous studies, these compounds have proven to be excellent anti-cancer, antitumor, antibacterial, antimicrobial and antioxidant agents. Monocarbohydrazones, as one of the carbohydrazone derivatives, have been slightly explored. Due to that reason, in this study, eight newly synthesized monocarbohydrazones were subjected to examinations by the use of three antioxidant tests. To determine the effectiveness of monocarbohydrazone as potential radical scavengers, DPPH (2,2-Diphenyl-1-picrylhydrazyl), ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) and FRAP (Ferric Reducing Antioxidant Power) assays were used. The obtained results could open the door for further studies of these compounds as biologically active substances.